Answer:
see explanation
Explanation:
Given
(2x + 4)(3x - 2) = 0
Equate each factor to zero and solve for x
2x + 4 = 0 ( subtract 4 from both sides )
2x = - 4 ( divide both sides by 2 )
x = - 2
3x - 2 = 0 ( add 2 to both sides )
3x = 2 ( divide both sides by 3 )
x =
![(2)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jgft8n5xwx5uidfnxss9gbutm3s8nfmtko.png)
Hence
smaller x = - 2
larger x =
![(2)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jgft8n5xwx5uidfnxss9gbutm3s8nfmtko.png)